Life Cycle Environmental Performance of B100 Biodiesel from Reutealis Trisperma (Kemiri Sunan): An Integrated Carbon Payback Period and Nature-Based Solutions Assessment - Kiki Hakiki; Dedi Priadi (Politeknik Siber Cerdika Internasional, 2026)
Background: Rising greenhouse gas emissions have increased the need for sustainable biofuels. Biodiesel from the non-edible feedstock Reutealis trisperma (kemiri sunan) offers a low-carbon alternative compatible with marginal lands under the Nature-Based Solutions (NbS) framework. Objective: This study evaluates the environmental performance of B100 biodiesel production from kemiri sunan and quantifies the effects of renewable energy integration on emission reduction, energy efficiency, and carbon payback. Methods: A Life Cycle Assessment (LCA) using a cradle-to-gate system boundary (functional unit: 1 liter of B100 biodiesel) was conducted using OpenLCA with the Ecoinvent 3.11 database, ReCiPe 2016 Midpoint (H), IPCC 2013, and Cumulative Energy Demand methods. The assessment covered the entire production chain from cultivation to bio-additive blending. Results: The carbon emissions of kemiri sunan B100 biodiesel were 2.04 kg CO₂-eq per liter, which were significantly lower than those of fossil diesel (3,400 kg CO₂-eq/ton) and comparable to palm oil biodiesel (1,659 kg CO₂-eq/ton). Transitioning to solar photovoltaic (PV) electricity reduced emissions by 56% (from 2.02 to 0.74 kg CO₂-eq). Energy balance indicators, including Net Energy Gain (NEG), Net Energy Ratio (NER), and Specific Energy Consumption (SEC), confirmed a positive energy output-to-input ratio. The Carbon Payback Period (CPP) was estimated at 11 years when using PLN electricity and was shortened to 6 years with solar PV integration. Conclusion: Kemiri sunan B100 biodiesel demonstrates strong potential as a sustainable, non-edible bioenergy source that supports low-carbon energy transitions. The integration of renewable energy, optimized cultivation management, and the utilization of degraded lands collectively enhance its environmental performance and strengthen the effectiveness of NbS implementation.